ACLD patients exhibit additional knee kinematic asymmetries at the speed level of healthy subjects - Kong, Lingchuang; Yang, Tao; Wang, Qing; Ou, Yongliang; Huang, Huayang; Huang, Wenhan; Zhang, Tao; Zhang, Yu; Zeng, Xiaolong (Frontiers in Bioengineering and Biotechnology, 2022)
Anterior cruciate ligament deficiency (ACLD) patients tend to walk slowly but try to catch up with the speed level of healthy subjects daily. Exploring the effects of the walking speed level of healthy subjects on the ACLD patients’ knee kinematics is important to improving non-operative treatments and delaying the progression of posttraumatic knee osteoarthritis. This study aimed to explore whether healthy controls’ walking speed level leads to additional knee kinematic asymmetries in patients with ACLD. 27 ACLD patients and 29 healthy controls were recruited for the study. The ACLD patients walked at two levels of walking speed, including self-selected and healthy controls’ walking speed levels. A three-dimensional gait analysis system was used to collect their knee kinematic data. ACLD patients exhibited more kinematic asymmetries when walking at healthy controls’ walking speed level than at their self-selected speeds. The kinematic asymmetries included increased posterior tibial translation (4.6mm) and anteroposterior tibial ROM (3.9mm), abduction angle (1.5°), and distal tibial translation (3.2mm) asymmetries (p<0.05). Our findings are meaningful for developing non-operative treatment strategies for patients with ACLD. To get fewer knee kinematic asymmetries, self-selected walking speed could be suggested for patients with ACLD daily rather than the speed levels of healthy subjects.